2005
DOI: 10.1161/01.str.0000189633.33623.69
|View full text |Cite
|
Sign up to set email alerts
|

The Third Stroke Registry in Tartu, Estonia

Abstract: Background and Purpose-The purpose of the present study was to estimate the time trends of stroke during the last 10 years in an Estonian population by comparison of the results from the 2 previous stroke registries from Tartu. Methods-The Third Stroke Registry in Tartu was conducted from January 12, 2001, to November 30, 2003. The previous registry was composed from January 1, 1991, to December 31, 1993. The design of both studies is similar, using the same study criteria and classification schemes. Results-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 22 publications
4
31
1
1
Order By: Relevance
“…In our Afro-Caribbean population, ERMANCIA II study showed significant decline of 30% in age-adjusted FESs incidence rate overtime. This trend mirrors those reported in previous studies [4][5][6]19,20 and supports evidence that Martinique belongs to the group of high-income countries. 3 As previously reported in black population, 21,22 we found a high prevalence of hypertension and diabetes mellitus.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our Afro-Caribbean population, ERMANCIA II study showed significant decline of 30% in age-adjusted FESs incidence rate overtime. This trend mirrors those reported in previous studies [4][5][6]19,20 and supports evidence that Martinique belongs to the group of high-income countries. 3 As previously reported in black population, 21,22 we found a high prevalence of hypertension and diabetes mellitus.…”
Section: Discussionsupporting
confidence: 90%
“…Conflicting results are reported on case-fatality rates. Register-based studies usually noted decline, 19,20 whereas population-based studies reported an overall stable rate. [4][5][6] Population-based epidemiological studies capture all patients with stroke including those with rapidly deteriorating symptoms who are not involved in trials assessing stroke unit management 36 and who may not be recognized in register-based studies.…”
Section: Strokementioning
confidence: 99%
“…Regarding data from Eastern Europe, incidence rates are similar to those from Tartu 14,15 In all comparisons, the different study periods need to be observed.…”
Section: Discussionmentioning
confidence: 88%
“…67,68 Although one study found that mean age at first stroke increased among women, and was unchanged among men, 20 many studies have shown a trend toward higher age in both sexes with time. 24,39,67 Some studies have shown an unchanged mean age, 30,32 and one study even a declining age at first-ever stroke. 66 …”
Section: Secular Trendsmentioning
confidence: 98%